Development of 3D Book Media Based on Pop Up Books to Increase Student Learning Motivation in Mathematics Learning in Grade IV Elementary Schools - Rini Irmata Putri; Siti Aisyah; Alfroki Martha (FKIP - Universitas Riau, 2026)
This research is motivated by the limited use of interesting and interactive learning media in Mathematics learning, which has an impact on low student learning motivation. This study aims to develop a valid, practical, and effective Pop Up Book-based 3D Book media in increasing student learning motivation. The study uses the Research and Development method with a 4D model that includes the define, design, develop, and disseminate stages. The research subjects were fourth-grade students at SD Kemala Bhayangkari, SDN 17 Gunung Pangilun, and SDN 03 Alai. The research instruments included validation sheets from media, language, and material experts, teacher and student practicality questionnaires, and pretest and posttest tests. The results showed that the media was in the very valid category with a validity percentage of 92.5% from media experts and 90% from language experts, and very practical with teacher and student responses above 89%. The effectiveness test through N-Gain analysis showed a value of 0.8111 very effective at SD Kemala Bhayangkari Padang, 0.7212 very effective at SDN 17 Gunung Pangilun, and 0.8897 very effective at SDN 03 Alai, so that the developed media is suitable for use in fourth grade Mathematics learning and supports the implementation of the Independent Curriculum.